The Role of Small and Medium Enterprises in Local Economic Development: A Case Study of Tanjung Jabung Timur, Jambi Province - Marlita; Wargo; Zaenal Abidin (Zabags International Journal of Islamic Studies, 2025)
This study examines the strategic role of Small and Medium Enterprises (SMEs) in driving local economic development in Tanjung Jabung Timur, Jambi Province, against a backdrop of place-based development imperatives and underutilized local resources. The research aims to (1) identify the contributions of SMEs to job creation, household income, and local economic structure, and (2) analyze the enabling and constraining factors affecting SME development, including access to finance, technology, market, and managerial capacity. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document review with SME owners, local government officials, and relevant stakeholders, and analyzed using thematic coding and triangulation. Findings indicate that SMEs substantively contribute to employment and income generation and strengthen local value chains by leveraging local raw materials, yet their growth is constrained by limited financing options, weak managerial skills, low adoption of digital marketing, and episodic institutional support. The study contributes conceptually by integrating local economic development, SME roles, and community empowerment frameworks, and offers practical recommendations for capacity building, inclusive financing schemes, and policy measures to enhance SME-driven, sustainable local development.